Dispersion Curves of Love Waves in Elastic Waveguides Loaded with a Newtonian Liquid Layer of Finite Thickness - Piotr KIEŁCZYŃSKI; Marek SZALEWSKI; Andrzej BALCERZAK; Krzysztof WIEJA (Archives of Acoustics, 2020)
In this paper, the authors analyse the propagation of surface Love waves in an elastic layered waveguide (elastic guiding layer deposited on an elastic substrate) covered on its surface with a Newtonian liquid layer of finite thickness. By solving the equations of motion in the constituent regions (elastic substrate, elastic surface layer and Newtonian liquid) and imposing the appropriate boundary conditions, the authors established an analytical form of the complex dispersion equation for Love surface waves. Further, decomposition of the complex dispersion equation into its real and imaginary part, enabled for evaluation of the phase velocity and attenuation dispersion curves of the Love wave. Subsequently, the influence of the finite thickness of a Newtonian liquid on the dispersion curves was evaluated. Theoretical (numerical) analysis shows that when the thickness of the Newtonian liquid layer exceeds approximately four penetration depths 4δ of the wave in a Newtonian liquid, then this Newtonian liquid layer can be regarded as a semi-infinite half-space. The results obtained in this paper can be important in the design and optimization of ultrasonic Love wave sensors such as: biosensors, chemosensors and viscosity sensors. Love wave viscosity sensors can be used to assess the viscosity of various liquids, e.g. liquid polymers.